EFFECT OF HARMONICS ON A SOLID-ROTOR INDUCTION MOTOR (Journal of Engineering, 2006)
The paper records a study of an investigating the performance of a solid-rotor induction motor witha rectilinear inverter excitation to identify the effects of the associated time harmonics. Theperformance is determined experimentally by using a stator of a three-phase laboratory inductionmotor that is fitted with a solid-steel rotor and compared with the theoretical model developedwhich uses the Fourier components of the supply voltage waveform. Final conclusions are drawnfrom comparing motor performances with sinusoidal and inverter excitations. An equivalent circuitmodel is developed to determine the harmonic currents. The development of the theoretical modelmake use of the results of existing field analyses. Harmonic currents and other performance detailsincluding the possible interactions between the co-existing harmonics are determined and discussed.The measured values of torque, input current and power over full speed range with the two types ofexcitation are presented, and compared with the theoretical values. The waveforms of current, phaseand line voltages are analyzed experimentally and compared with simulation results. The theoreticalresults correlate well with measured results and the significant harmonic effects are identified